Effects of mediated communication on conflict behavior, resolution, and affect in romantic couples. (December 2021) - Ruppel, Erin K.; Cherney, Maura R.; Quinn, Samantha F.; Richards, Riley J.
Mediated communication such as text messaging influences how romantic couples engage in and perceive conflict interactions, but the precise nature of these effects is unclear. We randomly assigned 43 romantic couples to engage in a conflict interaction either face-to-face ( n = 23 couples) or using a text-based messaging application ( n = 20 couples). Participants completed self-report measures of positive and negative conflict behaviors (e.g., humor and hostility), perceived progress toward conflict resolution, and positive and negative affect (e.g., inspired and afraid). Participants who engaged in more positive conflict behaviors reported more progress toward conflict resolution and more positive affect. Positive conflict behaviors were lower in text-based than face-to-face interactions. Progress toward conflict resolution, positive and negative affect, and negative conflict behaviors did not differ between text-based and face-to-face conflict interactions. The findings highlight the utility of examining both positive and negative conflict behaviors in mediated conflict and suggest that future research should further examine when and how participants compensate for a lack of nonverbal cues in mediated conflict.